Analysis of care and education pathways of refugee and asylum‐seeking children in care in England: Implications for social work - O'Higgins, AA (John Wiley & Sons Ltd, 2018)
There are currently 4,560 refugee and asylum‐seeking children in care in England, but little is known about their care histories and educational outcomes. This study analysed the educational outcomes of unaccompanied refugee and asylum‐seeking children in care at age 16 (n  = 167) in 2013, using secondary data analysis. It compared their care histories and educational experiences with other children in care and those in the general population. Secondly, it used linear regression to determine what factors predict educational outcomes. Refugee and asylum‐seeking young people in care faced fewer difficulties than their peers in care or those in need, but they lagged behind children in the general population. Age at entry, placement type, Strengths and Difficulties Questionnaire scores, school type and mobility predicted attainment. Special educational needs (SEN), number of placements and absences did not. Better care planning and a greater understanding of SEN are required to enhance the well‐being of this population.